(untitled) (New York, 2007)
This groundbreaking reference presents state-of-the-art packaging techniques for high-power quantum-well laser arrays. These devices, with continuous-wave emission powers of several hundred watts, represent the most effective converters from electric energy into light ever created. Edited by two leading experts in the field, Quantum-Well Laser Array Packaging covers all critical issues related to material packaging problems and includes unique screening and packaging techniques not found in any other resource. Overview of Laser Diode Degradation Mechanisms • Strain Measurement • Laser Facet Inspection by Imaging Techniques • Failure Prediction of High-Power Laser Bars • Reduction of External Stresses by Improved Packaging Techniques • Degradation Modes and Related Defects in High-Power Laser Bars.
Keywords: Microelectronic packaging,Nanoscience,Quantum wells,High power lasers,Khoa học nano,Tia lazer cường độ cao